2012
DOI: 10.1603/en12185
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Woodborers <I>Monochamus carolinensis</I> and <I>Monochamus titillator</I> (Coleoptera: Cerambycidae) to Known Cerambycid Pheromones in the Presence and Absence of the Host Plant Volatile α-Pinene

Abstract: In recent years, several attractant pheromones have been identified for cerambycid beetles, including 2-(undecyloxy)-ethanol (hereafter monochamol) for Monochamus galloprovincialis (Olivier), M. alternatus Hope, and M. scutellatus (Say). This study screened eight known cerambycid pheromones or their analogues (including monochamol) as potential attractants for M. carolinensis Olivier and M. titillator (F.), in the presence and absence of the host volatile α-pinene. Monochamol attracted M. carolinensis in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 54 publications
1
55
0
Order By: Relevance
“…Means within subfamilies with different letters (sexes combined) are signiÞcantly different (REGWQ means separation test, P Ͻ 0.05). 2011, Allison et al 2012, Fierke et al 2012, MaciasSamano et al 2012, Pajares et al 2013, attracted one Monochamus species and four lamiine species in different genera. This Þnding is in marked contrast to studies conducted in North America and Europe, where extensive Þeld trials using 2-(undecyloxy)ethanol as a lure have not attracted any lamiine species in genera other than Monochamus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Means within subfamilies with different letters (sexes combined) are signiÞcantly different (REGWQ means separation test, P Ͻ 0.05). 2011, Allison et al 2012, Fierke et al 2012, MaciasSamano et al 2012, Pajares et al 2013, attracted one Monochamus species and four lamiine species in different genera. This Þnding is in marked contrast to studies conducted in North America and Europe, where extensive Þeld trials using 2-(undecyloxy)ethanol as a lure have not attracted any lamiine species in genera other than Monochamus.…”
Section: Discussionmentioning
confidence: 99%
“…Pheromone structures also appear to be highly conserved among closely related cerambycid species. For example, pheromones of many species in the subfamily Cerambycinae are composed of 6-to 10-carbon 3-hydroxyalkan-2-ones, 2-hydroxyalkan-3-ones, or 2,3-alkanediols , whereas those of species in the subfamily Lamiinae (including species of Monochamus and Anoplophora glabripennis [Motschulsky]) consist of hydroxyethers and related compounds (Zhang et al 2002, Pajares et al 2010, Teale et al 2011, Allison et al 2012, Fierke et al 2012, Macias-Samano et al 2012. For the subfamily Spondylidinae and some species in the subfamily Lamiinae, the terpenoid (E)-6,10-dimethylundeca-5,9-dien-2-ol (hence fuscumol) and its corresponding acetate constitute pheromone components that are shared by a number of species (Silk et al 2007, Fonseca et al 2010, Mitchell et al 2011.…”
mentioning
confidence: 99%
“…These pheromones are produced by males and attract both sexes (see references below). The following chemicals were used in trap lures (references are relevant for cerambycid species of east-central Illinois, and provide sources of chemicals): ( RS )-3-hydroxyhexan-2-one, the R enantiomer of which is a pheromone component of many cerambycine species in the tribes Anaglyptini, Callidiini, Elaphidiini, and especially Clytini, and at least an attractant for many other species in these and other tribes (e.g., Lacey et al 2004, 2007, 2008, 2009; Hanks and Millar 2013), Syn - and anti -2,3-hexanediol, specific enantiomers of which are pheromone components of cerambycine species in the tribes Curiini, Clytini, and Elaphidiini (e.g., Lacey et al 2004, 2008, 2009),( E/Z )-6,10-dimethyl-5,9-undecadien-2-ol and ( E/Z )-6,10-dimethyl-5,9-undecadien-2-yl acetate (fuscumol and fuscumol acetate), attractants and probable pheromones of many species in the lamiine tribes Acanthocini and Acanthoderini (Mitchell et al 2011),2-(undecyloxy)-ethanol (monochamol), pheromone of the lamiine Monochamus carolinensis (Olivier) (Allison et al 2012) and a number of congeners (Pajares et al 2010, Teale et al 2011, Fierke et al 2012),2-methylbutan-1-ol, enantiomers of which are pheromone components of the early-season cerambycine Megacyllene caryae (Gahan), tribe Clytini, and cerambycine species in the genus Phymatodes , tribe Callidiini (Hanks et al 2007, 2012),Citral, an isomeric blend of neral and geranial, important pheromone components of M. caryae (Lacey et al 2008),Ethanol and α-pinene, plant volatiles that may attract certain cerambycid species, or enhance attraction to pheromones (Hanks et al 2012, Hanks and Millar 2013). …”
Section: Methodsmentioning
confidence: 99%
“…2-(undecyloxy)-ethanol (monochamol), pheromone of the lamiine Monochamus carolinensis (Olivier) (Allison et al 2012) and a number of congeners (Pajares et al 2010, Teale et al 2011, Fierke et al 2012),…”
Section: Methodsmentioning
confidence: 99%
“…To date, invasions have been demarcated and monitored using traps baited with an attractive mixture of volatile organic compounds (VOCs) produced by the host and two components of the male-produced aggregation-sex pheromone, 4-( n -heptyloxy)butan-1-ol and 4-( n -heptyloxy)butanal (e.g., Nehme et al 2010, 2014). This mixture, however, shows low efficacy of attraction (<100 specimens over multiple seasons; Meng et al 2014; Nehme et al 2014) compared to that of host VOC/pheromone blends that target related genera such as Monochamus (e.g., >2000 specimens, Allison et al 2012), which suggests that a more optimal mixture or attractant likely remains to be discovered. Female-associated VOCs (Wickham et al 2012), a trail pheromone (Hoover et al 2014), and a putative third component of the male-produced aggregation pheromone (Crook et al 2014) have been recently identified, although their effectiveness in monitoring invasion sites has yet to be tested.…”
Section: Introductionmentioning
confidence: 95%